Traditions & Customs of Ancient Indian Culture and Their Role in COVID 19 Pandemic Prevention and Control - Tiwari, Abhishek; Manar, Manish Kumar; Singh, Shivendra Kumar; Mohan, Udit; Panday, Kanchan; Mohan, Uday (Indian Journal of Community Health, 2020)
The truth of COVID 19 Pandemic is that it has already changed the demography of many countries, still changing the Climate & Environment and will continue to change the Global Economy for quite some time. The simple good personal hygiene and physical distancing measures were identified as one of the most effective protections against COVID 19. The Indian way of living has many scientific principles inherited in it to combat infectious diseases. We follow the Sanatan Sanskriti concepts traditionally, sometimes not even realizing the rationale behind it. This article tries to explore the correlation between the preventive measures and our traditional Sanatan practices. The pandemic has shaken the globe and time has come to rethink and move back to basics of our ancient traditions for a sustainable future. There is a need to promote our cultural practices and avoid running behind the ultra-modern ways of living so that the world learns to combat and live with the COVID 19.